Corporate core values and professional values of Generation Y from the perspective of the effectiveness of ethics programs = Kluczowe wartości firmy a zawodowe wartości pokolenia Y z perspektywy skuteczności programów etycznych - Stankiewicz, Janina; Łychmus, Patrycja (Zielona Góra: Faculty of Economics and Management Press)
In order for a business activity to be ethical, one needs ethical employees. Nevertheless, the ongoing generational change leads to the situation in which the values and the resulting standards of ethical behavior that have been thus far embraced in the workplace may no longer be unacceptable or respected by young people that enter the labor market.
Keywords: wartości firmy; katalog wartości; programy etyczne; pokolenie X; pokolenie Y